Magical criticism : the recourse of savage philosophy - Bracken, Christopher (University of Chicago Press, 2007)
During the Enlightenment, Western scholars racialized ideas, deeming knowledge based on reality superior to that based on ideality. Scholars labeled inquiries into ideality, such as animism and soul-migration,?savage philosophy,? a clear indicator of the racism motivating the distinction between the real and the ideal. In their view, the savage philosopher mistakes connections between signs for connections between real objects and believes that discourse can have physical effects?in other words, they believe in magic. Christopher Bracken?s Magical Criticism brings the unacknowledged history o.